河北省水利投融资体制改革思路及相关问题研究 = Reforming investment and financing system of water industry in Hebei - 位铁强 Wei, Tieqiang (2008)
This paper comprehensively analyzes the investment and finance system of water industry in Hebei province with economic theories about property right, competition and oligopoly, and infrastructure. Based on this analysis, we put forward the direction, target and principal for the reform of the investment and finance system of water industry.